The Influence of Financial Behavior with Risk Perception as Moderation in Determining Investment Decisions in Batam City - Lydia Desrita; Dewi Khornida Marheni (Politeknik Negeri Bengkalis, 2022)
Stock investment is now an alternative for young people to invest in. In investing in stocks, there are still factors that can hinder investors, namely financial behavior. The purpose of this research is to know and understand the financial factors and the perception of investors' risk on investment decisions in Batam City. This study uses a quantitative approach with primary data in the form of a questionnaire and using purposive sampling. Financial literacy, overconfidence, herding, anchoring, representative, and availability have a significant positive effect on investment decisions. Meanwhile, risk perception and the other six moderating variables don’t have any influence on investors' investment decisions. In investing, investors must understand financial behavior that helps investors in making good decisions and risk perception will make investors afraid of the risks that occur in investing.